Pan-cancer analysis of TMED2: unraveling potential immune characteristics and prognostic value in cancer therapy - Wang, Zhuangzhi; Sun, Changning; Wang, Pengfei; Lin, Shouyang; Wu, Xiao; Gu, Yuchao (Frontiers in Immunology, 2025)
BackgroundTransmembrane emp24 domain-containing protein 2 (TMED2) is involved in the sorting and transport of proteins between the Golgi apparatus and the endoplasmic reticulum. Recent research has identified a close association between TMED2 and tumorigenesis, yet its regulatory role and underlying mechanisms in pan-cancer signaling pathways remain unexplored.MethodsWe conducted a comprehensive pan-cancer analysis of TMED2 using multiple public databases. These analyses included assessments of prognostic significance, gene mutations, pathway enrichment, single-cell sequencing analysis, immune characteristics, co-expressed gene PPI network analysis, as well as the therapeutic response of TMED2 in immunotherapy and small molecule sensitivity. Finally, we examined the role that TMED2 plays at the cellular level.ResultsOur results show that the mRNA levels of TMED2 differ significantly between cancerous and normal tissues and are closely associated with cancer prognosis. Specifically, in CESC, MESO, LGG, and UVM, overexpression of TMED2 correlates with patient prognosis and various clinical pathological features. TMED2 is significantly associated with immune infiltration (including endothelial cells, neutrophils, dendritic cells, and eosinophils), immune checkpoints (CD274, HAVCR2, PDCD1LG2, and SIGLEC15), and signaling pathways (cell cycle and PI3K/Akt). Single-cell sequencing reveals that TMED2 is predominantly expressed in tumor cells of cervical cancer, glioma, and mesothelioma. Enrichment analysis shows that genes co-expressed with TMED2 are primarily involved in processes like endoplasmic reticulum stress and the ERAD pathway. Furthermore, cellular studies indicated that TMED2 expression promotes the growth, migration and invasion of glioma cells.ConclusionOur integrated analysis suggests that targeting TMED2, along with its associated genes and signaling pathways, could represent a new strategy for cancer immune treatment.